Effect of Hydrophilicity/Hydrophobicity of the Injector Wall on Atomization Performance - Xiaoyu Zhang; Xiaolei Zhang; Runze Duan; Lujia Liu (International Journal of Aerospace Engineering)
Hydrophilicity/hydrophobicity is a common physical property of the material. Water droplets roll on lotus leaf, and a lot of dust and dirt on the surface of the lotus leaf will be taken away, playing a certain cleaning role. The hydrophobic surface has drag reduction effect that would produce slip on the hydrophobic wall. There are some studies on hydrophilicity/hydrophobicity in channels, most of which focus on the effect of surface drag reduction and heat transfer on microchannels. However, few people pay attention to the effect of the hydrophilicity/hydrophobicity of the injector inner wall on the atomization performance. In this paper, three groups of the open-end swirl injector with different tangential channels were designed to study the effect of hydrophilicity/hydrophobicity on atomization performance. The hydrophobic coating was prepared and used on the inner wall of the injector, and the atomization experimental system was built. In the experiment, the liquid film thickness was measured using the conductance method. Details of the liquid film breakup and spray development were recorded with a high-speed camera. The average droplet diameter was measured by the Malvern particle size analyzer. The atomization performance of injectors with different tangential channels on the hydrophilicity/hydrophobicity was compared, and the effect of the velocity profile on the jet stability is discussed.